A Recreational Boating Characterization of Brevard County - Charles Sidman; Tim Fik; Robert Swett; Bill Sargent; James Fletcher; Susan Fann; David Fann; Alisa Coffin (EDIS)
TP-160 is a 129-page illustrated report by Charles Sidman, Tim Fik, Robert Swett, Bill Sargent, James Fletcher, Susan Fann, David Fann, and Alisa Coffin. It documents the methods, procedures, and results of a map-based mail survey that was distributed to Brevard County boaters to obtain seasonal information about their boating preferences, use profiles, and travel patterns. Published by the UF Sea Grant College Program, September 2007.